A Vital Question for Contemporary South Africans: SM Mofokeng's Senkatana. Issue 1 (2nd January 2021) - Dunton, Chris
Abstract : This article examines SM Mofokeng's play Senkatana as a version of the legend of Kgodumodumo and Senkatana, earlier versions of which are summarised to provide comparative contextualisation and to clarify Mofokeng's thematic priorities in constructing his text. The discussion of the play focuses on its dependence on oratory, but more especially on the way it projects parallels between Senkatana's life and death and those of Christ, and on the contemporary relevance of the play. Throughout, parallels are drawn between Senkatana and other texts in the Africa Pulse series of translations of southern African classics; there is, too, some comment on the processes of literary translation.